Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\left(\dfrac{1}{2}-1\right)\left(\dfrac{1}{3}-1\right)\left(\dfrac{1}{4}-1\right)...\left(\dfrac{1}{2015}-1\right)\left(\dfrac{1}{2016}-1\right)\left(\dfrac{1}{2017}-1\right)\\ A=\left(-\dfrac{1}{2}\right).\left(-\dfrac{2}{3}\right).\left(-\dfrac{3}{4}\right)...\left(-\dfrac{2014}{2015}\right)\left(-\dfrac{2015}{2016}\right)\left(-\dfrac{2016}{2017}\right)\\ A=\dfrac{1.2.3.4...2014.2015.2016}{2.3.4...2015.2016.2017}=\dfrac{1}{2017}\)
\(B=\left(-1\dfrac{1}{2}\right)\left(-1\dfrac{1}{3}\right)\left(-1\dfrac{1}{4}\right)...\left(-1\dfrac{1}{2015}\right)\left(-1\dfrac{1}{2016}\right)\left(-1\dfrac{1}{2017}\right)\\ B=\left(-\dfrac{3}{2}\right)\left(-\dfrac{4}{3}\right)\left(-\dfrac{5}{4}\right)...\left(-\dfrac{2016}{2015}\right)\left(-\dfrac{2017}{2016}\right)\left(-\dfrac{2018}{2017}\right)\\ B=\dfrac{3.4.5...2016.2017.2018}{2.3.4...2015.2016.2017}=\dfrac{2018}{2}=1009\)
\(M=A.B=\dfrac{1}{2017}.1009=\dfrac{1009}{2017}\)
\(A=\dfrac{1}{1.2.3}+\dfrac{1}{2.3.4}+....+\dfrac{1}{18.19.20}=\dfrac{1}{2}\left(\dfrac{1}{1.2}-\dfrac{1}{2.3}+\dfrac{1}{2.3}-\dfrac{1}{3.4}+...+\dfrac{1}{18.19}-\dfrac{1}{19.20}\right)\\ =\dfrac{1}{2}\left(\dfrac{1}{2}-\dfrac{1}{19.20}\right)\\ =\dfrac{1}{4}-\dfrac{1}{2.19.20}< \dfrac{1}{4}\)
Cái B TT nhé
\(\dfrac{1}{2^2}+\dfrac{1}{3^2}+....+\dfrac{1}{n^2}< \dfrac{1}{1.2}+\dfrac{1}{2.3}+...+\dfrac{1}{\left(n-1\right)n}\\ =1-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{3}+...+\dfrac{1}{n-1}-\dfrac{1}{n}\\ =1-\dfrac{1}{n}< 1\)
D TT
E mk thấy nó ss ớ
a,
\(\left(4x-\dfrac{1}{3}\right)^6=1\\ \Rightarrow\left[{}\begin{matrix}4x-\dfrac{1}{3}=1\\4x-\dfrac{1}{3}=-1\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}4x=\dfrac{4}{3}\\4x=\dfrac{-2}{3}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\dfrac{1}{3}\\x=\dfrac{-1}{6}\end{matrix}\right.\)
b,
\(\left(5x-\dfrac{2}{3}\right)^2=0\\ \Rightarrow5x-\dfrac{2}{3}=0\\ 5x=\dfrac{2}{3}\\ x=\dfrac{2}{15}\)
c,
\(\left(\dfrac{1}{3}x-\dfrac{1}{2}\right)^3=-8\\ \Rightarrow\dfrac{1}{3}x-\dfrac{1}{2}=-2\\ \dfrac{1}{3}x=\dfrac{-3}{2}\\ x=\dfrac{-9}{2}\)
d,
\(\dfrac{81}{3^n}=3\\ \Leftrightarrow3^4:3^n=3^1\\\Leftrightarrow3^{4-n}=3^1 \\ \Rightarrow n=3\)
e,
\(\dfrac{\left(-2\right)^x}{64}=-2\\ \Leftrightarrow\left(-2\right)^x:\left(-2\right)^6=\left(-2\right)^1\\ \Leftrightarrow\left(-2\right)^{x-6}=\left(-2\right)^1\\ \Rightarrow x=7\)
f,
\(\left(-20\right)^n:10^n=16\\ \left[\left(-20\right):10\right]^n=16\\ \left(-2\right)^n=\left(-2\right)^4\\ \Rightarrow n=4\)
Bài 1:
a) \(\left(4x-\dfrac{1}{3}\right)^6=1\)
\(\Rightarrow4x-\dfrac{1}{3}=1\)
\(4x=1+\dfrac{1}{3}\)
\(4x=\dfrac{4}{3}\)
\(x=\dfrac{4}{3}:4\)
\(x=\dfrac{1}{3}\)
b) \(\left(5x-\dfrac{2}{3}\right)^2=0\)
\(\Rightarrow5x-\dfrac{2}{3}=0\)
\(5x=\dfrac{2}{3}\)
\(x=\dfrac{2}{3}:5\)
\(x=\dfrac{2}{15}\)
c) \(\left(\dfrac{1}{3}x-\dfrac{1}{2}\right)^3=-8\)
\(\Rightarrow\left(\dfrac{1}{3}x-\dfrac{1}{2}\right)^3=\left(-2\right)^3\)
\(\dfrac{1}{3}x-\dfrac{1}{2}=-2\)
\(\dfrac{1}{3}x=-2+\dfrac{1}{2}\)
\(\dfrac{1}{3}x=\dfrac{-3}{2}\)
\(x=\dfrac{-3}{2}:\dfrac{1}{3}\)
\(x=\dfrac{-9}{2}\)
d) \(\dfrac{81}{3^n}=3\)
\(\Rightarrow\dfrac{3^4}{3^n}=3\)
\(\Rightarrow3^n.3=3^4\)
\(3^{n+1}=3^4\)
n + 1 = 4
n = 4 - 1
n = 3
e) \(\dfrac{\left(-2\right)^x}{64}=-2\)
\(\Rightarrow\dfrac{\left(-2\right)^x}{\left(-2\right)^6}=-2\)
\(\Rightarrow\left(-2\right)^x=\left(-2\right)^6.\left(-2\right)\)
\(\left(-2\right)^x=\left(-2\right)^7\)
x = 7
f) (-20)n : 10n = 16
(-20 : 10)n = 16
(-2)n = 16
(-2)n = (-2)4
n = 4.
\(\dfrac{1}{3}+\dfrac{1}{6}+...+\dfrac{2}{n\left(n+1\right)}=\dfrac{2}{6}+\dfrac{2}{12}+...+\dfrac{2}{n\left(n+1\right)}\)
\(=\dfrac{2}{2.3}+\dfrac{2}{3.4}+...+\dfrac{2}{n\left(n+1\right)}\)
\(=2.\left(\dfrac{1}{2.3}+\dfrac{1}{3.4}+...+\dfrac{1}{n\left(n+1\right)}\right)\)
\(=2.\left(\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{3}-\dfrac{1}{4}+...+\dfrac{1}{n}-\dfrac{1}{n+1}\right)\)
\(=2.\left(\dfrac{1}{2}-\dfrac{1}{n+1}\right)=\dfrac{2016}{2017}\)
\(\Rightarrow\dfrac{2016}{2017}:2=\dfrac{1}{2}-\dfrac{1}{n+1}\)
\(\dfrac{1008}{2017}=\dfrac{1}{2}-\dfrac{1}{n+1}\)
\(\Rightarrow\dfrac{1}{n+1}=\dfrac{1}{4034}\)
=>n+1=4034
n=4034-1
n=4033